Synthesis of acyloxyl pyrazolines by copper-mediated aminoacyloxylation of unsaturated ketohydrazones. Issue 28 (2nd July 2018) - Chen, Manman; Qi, Lin; Chen, Jia-Min; Ren, Pei-Xing; Du, Jie; Wang, Li-Jing; Li, Wei
Abstract : An efficient copper-mediated aminoacyloxylation of unsaturated hydrazones has been developed. Copper carboxylates serve as both reaction promoters and carboxylate sources in these easily conducted reactions. This method provides straightforward access to diversely useful acyloxyl pyrazolines. Abstract : An efficient and step-economical copper-mediated intra-/intermolecular aminoacyloxylation of β, γ-unsaturated hydrazones has been developed. Copper carboxylates serve as both reaction promoters and carboxylate sources in these easily conducted reactions. This method provides straightforward access to diversely useful acyloxyl pyrazolines, which are hard to access traditionally, in good to excellent yields.